2020
DOI: 10.1080/07481187.2020.1808737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mortality awareness on attitudes toward dying and death and meaning in life—a randomized controlled trial

Abstract: A randomized controlled trial was carried out to investigate effects of heightened mortality awareness on meaning in life and attitudes toward dying and death. An intervention group (n ¼ 51) completed questionnaires and participated in interventions to increase mortality awareness; a control group (n ¼ 47) only completed the questionnaires. Longitudinal analyses revealed a decrease in the intervention group's fear of dying and an increase in their acceptance of dying, but no effects on attitudes toward death. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Several studies (e.g., Denckla et al, 2020;Spitzenstätter & Schnell, 2020;Tang et al, 2021) have shown that when a person acknowledges and embraces death awareness, it builds up one's psychological resilience and also enhances one's well-being when in face of mortality or death. That is to say when we confront our mortality, we are also cultivating a better appreciation of life despite its transient existence, prioritizing what truly matters most to us, and living more simply and authentically.…”
Section: Death Awareness and Dying: How Are The Two Related?mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies (e.g., Denckla et al, 2020;Spitzenstätter & Schnell, 2020;Tang et al, 2021) have shown that when a person acknowledges and embraces death awareness, it builds up one's psychological resilience and also enhances one's well-being when in face of mortality or death. That is to say when we confront our mortality, we are also cultivating a better appreciation of life despite its transient existence, prioritizing what truly matters most to us, and living more simply and authentically.…”
Section: Death Awareness and Dying: How Are The Two Related?mentioning
confidence: 99%
“…An example is someone who acknowledges his/her mortality may find comfort in the idea of creating a meaningful legacy, whether through positive contributions to others, artistic expression, or leaving a lasting impact on the community. With the acknowledgement of the transient nature of life, one comes to terms a sense of purpose in life and that helps to reduce the mental burden of existential distress (Spitzenstätter & Schnell, 2020).…”
Section: How Can Death Awareness Be Associated With Mental Wellness?mentioning
confidence: 99%
“…Supplemental analyses of Study 2 showed that belongingness partially mediated the effect of condition on meaning in life (See the Supplement pp. [25][26]. Authoritarian messages might enhance in-group favoritism and/or out-group hostility, and through these, subsequently affect perceptions of life's meaningfulness.…”
Section: Fostering Social Connectionmentioning
confidence: 99%
“…Typically measured with questionnaires, including items like, “I understand my life’s meaning,” and “My life has a clear sense of purpose” [ 22 ], self-reported meaning in life is associated, prospectively, with positive life outcomes across a variety of domains, including lower suicide risk, greater lifetime earnings, better survival rates after health crises, and reduced mortality [ 23 ]. Although meaning in life is relatively stable, it is a subjective feeling that can be affected by manipulations, including exposure to stimuli that make sense [ 24 ], reminders of the reality of death [ 25 , 26 ], social exclusion and ostracism [ 27 ] and mental simulation [ 28 ]. Thus, meaning in life can fluctuate in response to changing circumstances [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on research among Afghani families, Eggerman and Panter-Brick (2010) contend that cultural values foster considerable psychosocial strain as people rectify individual versus collective decisions. Moreover, what causes fear versus acceptance in illness and death cannot be dissociated from how people perceive and communicate affliction ( Spitzenstätter and Schnell, 2020 ). This is in contrast to how Foucault (1990) perceived the use of medical knowledge to regulate behavior and reshape the self to adapt to a new biological reality.…”
Section: Introductionmentioning
confidence: 99%